Role of the cytoskeleton in flow (shear stress)-induced dilation and remodeling in resistance arteries - Loufrani, Laurent (Springer, 2008)
Cytoskeletal proteins determine cell shape and integrity and membrane-bound structures connected to extracellular components allow tissue integrity. These structural elements have an active role in the interaction of blood vessels with their environment. Shear stress due to blood flow is the most important force stimulating the endothelium. The role of cytoskeletal proteins in endothelial responses to flow has been studied in resistance arteries using pharmacological tools and transgenic models. Shear stress activates extracellular “flow sensing” elements associated with a thick glycocalyx communicating the signal to membrane-bound complexes (integrins and/or dystrophin-dystroglycans) and to eNOS through a pathway involving the intermediate filament vimentin, the microtubule network and actin. When blood flow increases chronically the endothelium triggers diameter enlargement and medial hypertrophy. This is facilitated by the genetic absence of the intermediate filaments, vimentin and desmin suggesting that these elements oppose the process.